Optimal integration of demand response programs and electric vehicles in coordinated energy management of industrial virtual power plants. (September 2021) - Azimi, Zahra; Hooshmand, Rahmat-Allah; Soleymani, Soodabeh
Highlights: A new method has been presented for planning IVPPs in light of synchronous presence of DR programs and EV. An effective and economical EMS has been proposed for integrating DERs and numerous electrical loads. The stochastic EMS is presented to maximize the profits accrued on IVPP. The IVPP is comprised of conventional power plants, wind power plants, photovoltaics, DR programs, and EV. The IVPP is comprised of conventional power plants, wind power plants, photovoltaics, demand response programs, and EVs. Abstract: Today, implementation of an efficient and economical energy management system (EMS) in industrial smart grids- given the rising trend in electrical load consumption and restrictions in ramping up the power plants' capacities- cannot be underestimated. Optimal planning avails itself of the exploitation manner of existing energy resources alongside appropriate employment of demand response (DR) programs and available electric vehicles (EV) in parking lots of immense industrial centers as storage sites in energy management systems in industrial smart grids have been seriously considered. This article introduces a new perspective in the simultaneous use of demand response loads and available electric vehicles in parking lots toward energy management of industrial virtual power plants (IVPPs) aiming at augmenting the system's profits as well as increasing the grid reliability under peak load conditions and cutting down on industrial centers load shedding. The objective function of the problem is formulated within the framework of short-term production planning for distributed energy resources (DER) and conventional ones in conjunction with DR programs and EV in such a way that the IVPPs' profits are maximized. In order to validate the performance of the proposed method, we have applied and tried on the second zone of IEEE-RTS standard grid. The outcomes accrued from various simulations point to the fact that the presence of EV within the boundaries of EV's parking lots prompts considerable increase in IVPPs' storage amount and consequent decline in exploiting full power grid capacity. Utilizing DR programs for responding load and selecting best scheduling schemes for each IVPP during various times of a day-night cycles will bring about a reduction in operation costs, de-peaking as well as an enhanced performance of EV's parking installations. Graphical abstract: Image, graphical abstract